Bidirectional regulation of zinc embedded titania nanorods: antibiosis and osteoblastic cell growth. Issue 19 (30th January 2015) - Cheng, Haoyan; Mao, Lin; Wang, Lele; Hu, Hao; Chen, Yangyang; Gong, Zheni; Wang, Chengjun; Chen, Jisheng; Li, Rui; Zhu, Zhihong
Abstract : A bifunctional regulation in antibiosis and osteoblastic cell growth is achieved by well-organized TiO2 –Zn nanoarrays. Abstract : New generation bone implants with favourable biocompatibility and long-term antibacterial activity have attracted a great deal of attention due to their bifunctional regulation on osteogenesis and antibiosis, demonstrating great potential for their application in biomedical science. In this study, Zn-incorporated TiO2 nanoarrays are prepared by a hydrothermal approach and the Zn content in the nanorod-structure scaffolds can be controlled by altering the concentration of the precursor solution, thereby tailoring the Zn incorporated scaffolds to meet the requirements in bifunctional clinical applications. Cytocompatibility of the Zn-incorporated TiO2 nanoarrays was evaluated by MTT, LDH and ALP assays, and all the results are found to be dependent on both time and Zn content. Among TiO2 –Zn nanoarrays, TiO2 –Zn0.2 has the most remarkably stimulative effects on MC3T3-E1 cells compared to untreated controls. Meanwhile, the antibacterial tests confirm that the hybrid nanoarrays can exert inhibitory effects on Escherichia coli ( E. coli, Gram-negative) and Staphylococcus aureus ( S. aureus, Gram-positive) to various degrees based on time and Zn content. The bifunctional implant materials that allow sustainable Zn release with both superior biocompatibility and long-term antibacterial properties will hold significant promise for scalable productions and open the horizon for further applications as biomedical devices.